CONSEQUENCES OF SHIFTWORKING ON SLEEP DURATION, SLEEPINESS, AND SLEEP ATTACKS - Ohayon, Maurice M.; Smolensky, Michael H.; Roth, Thomas (Chronobiology international, 2010)
Rotating shift and permanent night work arrangements are known to compromise sleep. This study examined the effects of work schedule on sleep duration, excessive sleepiness, sleep attacks, driving, and domestic professional accidents. A representative sample of the general population of the state of New York-3,345 individuals ≥18 yrs of age-was interviewed by telephone regarding their sleep and psychiatric and organic disorders. Multivariate models were applied to derive odds ratios (OR) after adjustment for age, sex, physical illness, mental disorders, obstructive sleep apnea, and sleep duration. On average (±SE), workers slept 6.7 ± 1.5 h, but 40% slept <6.5 h main sleep episode. Short-sleep duration (<6 h) was strongly associated with fixed night (OR: 1.7) and day-evening-night shiftwork arrangement (OR: 1.9). Some 20% of the workers manifested excessive sleepiness in situations requiring high attention, and it was associated with the fixed night (OR: 3.3) and day-evening-night work arrangements (OR: 1.5). Overall, 5% of the workers reported sleep attacks; however, they occurred three-times more frequently in the fixed night (15.3%) than other work arrangements (OR: 3.2). Driving accidents during the previous 12 months were reported by 3.6% of the workers and were associated with fixed night (OR: 3.9) and day-evening-night (OR: 2.1) work schedules. The findings of this study indicate that working outside the regular daytime hours was strongly associated with shorter sleep duration, sleepiness, and driving accident risk. Night work is the most disrupting, as it is associated with insufficient sleep during the designated rest span and excessive sleepiness and sleep attacks during the span of activity, with an associated consequence being increased driving accident risk. (Author correspondence: mohayon@stanford.edu)